Factors contributing to the implementation of interventions to prevent and manage intensive care unit delirium: a systematic review protocol - Roxanne M Parslow; Andrew Booth; Maria Pufulete; Andrew J Moore; Ben Gibbison; Burak Kundakci; Katherine Louise Jones (BMJ Open)
Introduction Delirium is a common and serious condition that frequently affects patients in the intensive care unit (ICU). It is characterised by an acute disturbance in cognition, attention and awareness that develops over a short period of time and tends to fluctuate in severity. Patients with ICU delirium (ICUD) may experience confusion, disorientation, difficulty focusing and perceptual disturbances such as hallucinations or delusions. The prevalence of ICUD is high, with estimates suggesting that it can affect up to 70% of ICU patients. The development of ICUD is associated with several adverse outcomes, including prolonged ICU and hospital stays, increased healthcare costs, higher mortality rates and an increased risk of long-term cognitive impairment, including dementia. It is unclear which components should be included in a complex intervention to prevent and manage ICUD. Furthermore, we need to understand how the different components have been implemented and their impact on clinical practice.Methods and analysis The review will be reported according to the Preferred Reporting Items for Systematic reviews and Meta-Analysis Protocols (PRISMA-P) and the enhancing transparency in reporting the synthesis of qualitative research (ENTREQ) reporting recommendations. We will perform systematic searches to identify relevant interventions and implementation strategies for the prevention or management of ICUD. We will assess primary research, service evaluations and audits for the use of the Standards for QUality Improvement Reporting Excellence (SQUIRE) as a checklist for quality improvement in healthcare. We will extract both qualitative and quantitative data and assess study quality using the Critical Appraisal Skills Programme (CASP) tool. Our findings will be synthesised using a best-fit framework synthesis mapped against the Theoretical Domains Framework (TDF). Our Patient and Public Involvement (PPI) group will contribute to the development of review processes such as the research question and methodology and will help to evaluate which outcomes are most important.Ethics and dissemination No ethical approval is required for this study. The results of this systematic review of implementation strategies will be disseminated through peer-reviewed publications and conferences. They will also form part of an evidence map and logic model for factors that can improve the implementation of strategies for prevention, identification and management of ICUD.PROSPERO registration number CRD42024537313.